(untitled) (Journal of Fiber Bioengineering and Informatics, 2008)
Ornithoctonus huwenna spiders can be bred in mass production, and potential applications of the spider silk in medical materials should be paid attentions. Regenerated nano-scale spider silk nonwovens were prepared by electrospinning from tanglesome Ornithoctonus huwenna spider silk. The morphologies of the electrospun spider silk fibers were investigated, and the cell compatibilities were explored. The results showed that the electric field strength was an important factor for the diameter, degree of crystal and molecular conformation of electrospun Ornithoctonus huwenna spider silk. With the increase of electric field strength, fibers became fine and even, and the crystallinity and